Improving Investment Decisions through Financial Knowledge - Sianipar, Gloria J M; Simanjuntak, Sri Ida Royani; Hasugian, Christnova; Tanjung, Ribka Chritiani (JURISMA : Jurnal Riset Bisnis & Manajemen, 2024)
The purpose of this study is to investigate how investing decisions are impacted by financial behavior, financial literacy, and emotional intelligence. Quantitative research is what this kind of study is. The data analyzed is primary data gathered from the responses of the millennial generation residing in Medan, who were given questionnaires using non-random sampling techniques. One hundred responders made up the research sample. The PLS (Partial Least Square) 4.0 software was used to analyze the data, which included the following characteristics: the millennial generation, which is composed of people aged 27 to 42 who reside in Medan, are productive, and earn personal income. The findings of this study indicate that while financial literacy and emotional intelligence factors have a favorable and significant impact on investing decisions, financial conduct has no discernible effect. For the millennial generation to be more inclined to invest and have sound financial standing in the future, financial literacy, and emotional intelligence require being further enhanced.